Improving the energetic utilization of household food waste: Impact of temperature and atmosphere during storage - Sailer, Gregor; Eichermüller, Johanna; Empl, Florian; Poetsch, Jens; Pelz, Stefan; Kuptz, Daniel; Oechsner, Hans; Müller, Joachim (Waste management (Elmsford), 2022)
[Display omitted] •Household food waste was monitored during storage to optimize energetic utilization.•Recipe-based and reproducible samples improved comparability of experiments.•Aerobic storage reduced energy contents drastically but lowered mass of waste.•Anaerobic storage has the potential to preserve energy contents almost completely.•Reduced energy losses during storage could improve energy yields in waste digestion. Food waste (FW) from households represents a major fraction of municipal waste and it is often collected in separate biowaste bins. Until waste collection is carried out, storage conditions in the biowaste bin influence FW properties. To draw conclusions for an optimized waste utilization in anaerobic digestion (AD), the aim of this study was to evaluate the impact of storage duration (20 to 40 days) and temperature (5 °C and 20 °C) on inherent energy potentials of household FW during aerobic and anaerobic storage. Therefore, physico-chemical parameters of recipe-based FW samples with reproducible initial compositions were monitored. After 20 days of aerobic storage, water contents (WC) were reduced from 61.9% to 39.5% (20 °C) and from 63.9% to 50.3% (5 °C) while organic dry matter (oDM) concentrations were lowered by 4.3% (20 °C) and 1.1% (5 °C). Increased pH-values of 6.6 (initially 5.5) were only measured for FW stored aerobically at 20 °C. In total, the energy potential was decreased by 31% (20 °C) and by 16% (5 °C). Thus, storage temperature and duration are crucial parameters for optimized aerobic FW storage leading to higher energy yields in AD. Instead, anaerobic storage of FW decreased pH-values to <5 while increasing WC in all samples (up to 67% at 20 °C). As oDM concentrations were preserved almost completely, the energy potential losses were only marginal proving that energy contents of FW could be preserved at household level. Consequently, energy yields in AD of FW could be increased through anaerobic storage conditions.